Exploring the relationship between migrants’ purchasing of commercial medical insurance and urbanisation in China - Jinhua Liu; Hongsheng Chen; Yang Chen; Zhigang Li (BMC Health Services Research, 2018)
Abstract Background Over the past 40 years, the Chinese government has diligently promoted the market-oriented reform of the health insurance system. However, as it is affected by the urban-rural dual structure, most rural-to-urban migrants are excluded from local public health services and medical insurance schemes in the cities in which they live. Buying local commercial medical insurance (CMI) is an important way for migrants to obtain local medical services. Therefore, this study’s purposes were to explore the city factors that affect migrants’ purchase of CMI and to investigate the relationship between urbanisation and migrants’ purchase of CMI. Methods This study used the 2013 National Floating Population (Migrants) Dynamic Monitoring Survey data, which covered 31 provinces, municipalities, and autonomous regions in China. The respondents were migrants (15–59 years; n = 164,752) who lived in the inflow areas for more than a month without obtaining a local household registration record. We used city factors, neighbourhood factors, and individual factors that affect residents’ purchase of CMI to construct a theoretical framework and examined the effect of urbanisation on migrants’ choice of CMI using multilevel logistic regression. Results The proportion of migrants who had local or hometown CMI was 5.70%; most migrants had no CMI (94.30%). Of these, 4.42% had CMI in the city in which they live (i.e. local CMI) and 1.64% had CMI in their hometown (i.e. hometown CMI). Migrants living in first-tier and third-tier cities were less likely to have CMI than those in second-tier cities (odds ratio [OR] = 0.454, 95% confidence interval [CI]: 0.395–0.521; OR = 0.588, 95% CI: 0.464–0.746). Furthermore, the regression results revealed a U-shaped relationship between the odds of migrants having CMI and the urbanisation rate of the prefecture-level cities. The findings also indicated that with higher socioeconomic status, there was a greater probability of purchasing CMI. Conclusions The improvement of urbanisation has a positive effect on migrants’ purchase of CMI. However, China’s medical insurance market is still underdeveloped. It is necessary for the Chinese government to increase migrants’ participation rate in CMI to cover soaring medical expenses.